Quando é que essa pena vai acabar? narrativas sobre tráfico de drogas e encarceramento feminino no sistema prisional Paraibano - Tolentino, Graziela Mônica Pereira (2023)
This research aims to analyze how the experience of women criminalized for their involvement in work activities related to drug trafficking and who were sentenced to custodial sentences in the Prison System of Paraiba is constituted. The reflections are supported by the narratives of a group of women survivors of prison, granted through interviews, which report their experiences before, during and after prison, as well as how they are assisted by official programs aimed at this public, with a view to complying with the assistance measures provided for in the Penal Execution Law – LEP (Law No. 7210/1984). As inclusion criteria, women were selected who were subjected to the prison system in Paraíba in the closed regime, regardless of having been convicted. The theoretical basis is based on authors linked to Critical and Feminist Criminologies, who favor the discussion of how unequal relations of gender, race, class and territory intersect in women's lives through a patriarchal logic and a System of Criminal Justice, which has selected and punished women through the Drug Law (Law nº 11.343/2006). The study also uses socioeconomic data on incarceration in Brazil, especially from the National Penitentiary Information Survey – Infopen. To this end, the phenomenon of the "War on drugs" is discussed, presenting how it was constituted on the international scene and its influence on public security policies adopted in Brazil. The reflection goes on to analyze how the “War on drugs” materializes in female incarceration, resulting in the penalization of the most socially marginalized women, in a process of penal selectivity and feminization of poverty. The methodological route was conducted through an exploratory field research with a qualitative approach and, due to the particularities and complexities involving the theme of female incarceration due to involvement with drug trafficking, the Snowball technique was chosen as the main access path to the interlocutors. To focus on the content of the interviews, thematic analysis was used, in order to make it possible to organize the research material, ordering the main topics addressed in specific categories. As a result, it was possible to infer that the women interviewed, despite all having already served the length of incarceration legally stipulated within prison institutions, still did not consider themselves free. The consequences of deprivation of liberty for these women and their families go far beyond the search for work (formal and informal). For most of our interlocutors, leaving prison did not mean the end of the sentence imposed, showing how submission to prison contributes to maintaining the reproduction of social inequalities typical of the modern capitalist and patriarchal State. The results allow us to conclude that the criminalization processes, incremented from the ideological and normative framework of the War on Drugs, have found in gender, race and class markers their main definers of penal selectivity. This fact perpetuates and deepens pre-existing patterns of segregation and exclusion and signals that the condition of women in drug trafficking activities is a reflection and expression of the sexual division of labor and the conditions of social reproduction of the capitalist mode of production.